Role of multiheme cytochromes involved in extracellular anaerobic respiration in bacteria - Edwards, Marcus J. (2020)
Heme containing proteins are involved in a broad range of cellular functions, from oxygen sensing and transport to catalyzing oxidoreductive reactions. The two major types of cytochrome (b-type and c-type) only differ in their mechanism of heme attachment, but this has major implications for their cellular roles in both localization and mechanism. The b-type cytochromes are commonly cytoplasmic, or are within the cytoplasmic membrane, while c-type cytochromes are always found outside of the cytoplasm. The mechanism of heme attachment allows for complex c-type multiheme complexes, having the capacity to hold multiple electrons, to be assembled. These are increasingly being identified as secreted into the extracellular environment. For organisms that respire using extracellular substrates, these large multiheme cytochromes allow for electron transfer networks from the cytoplasmic membrane to the cell exterior for the reduction of extracellular electron acceptors. In this review the structures and functions of these networks and the mechanisms by which electrons are transferred to extracellular substrates is described.